Site Specific Stem Volume Models for Pinus patula and Pinus oocarpa - Herbert Malata; Elisha S. Ngulube; Edward Missanjo (International Journal of Forestry Research)
Sustainable management of timber forests requires availability and adequacy of models for accurate estimation of tree volumes. This study was conducted to develop site specific models for estimating individual total tree stem volume of Pinus patula and Pinus oocarpa at Chongoni Timber Plantation in Central Malawi. A total of 32 trees from Pinus patula compartment and 48 trees from Pinus oocarpa compartment were destructively sampled. Various predictors including diameter at breast height (dbh) and height (ht) were run against total stem volume using a nonlinear mixed-effects modelling approach. The results indicate that the developed site specific models showed a significant association between total stem volume and the predictors (dbh and ht). The developed volume models accounted for at least 99% of the total variation in the total stem volume data. This suggests that application of the developed site specific models is highly recommended when accurate results are required. The appropriateness of the developed models was also supported by the fact that the total relative errors (TRE) of these models were lower (range: −0.04% to 0.06%) than the TRE of some previously developed models (range: −12.40% to 41.70%) tested on the present data.